Lifestyle Identification and Random Blood Glucose Screening in Mulyorejo Public Health Center, Surabaya, Indonesia - Hariyono, Hariyono; Madyawati, Sri Pantja; Fauziyah, Shifa; Sucipto, Teguh Hari (International Journal of Scientific Research and Management (IJSRM), 2024)
Backgrounds: One of the non-communicable disease that still increase is Type 2 Diabetes Mellitus (T2DM). Of these, lifestyle pattern have been known as the risk factors. Objectives: This study aims to investigate lifestyle and conduct random blood glucose (RBG) screening in a community. Methods: Accidental sampling was conduct on November 12th to November 15th 2019 in Mulyorejo Public Health Center, Surabaya, Indonesia. Participants were investigate their lifestyle by self-questionnaire while RBG screening was done by using finger capillary test. Chi-square test was used to analyse the  relationship between lifestyle and level of RBG  Results:  The results shows that there’s no lifestyle variables that shows significantly associated with the level of RBG. Family history shows (p=0.15; p>0.05), blood pressure (p=0.91; p>0.05); smoking (p=0.26; p>0.05); physical activity (p=0.19; p>0.05); vegetable consumption (p=0.94; p>0.05); and fruit consumption (p=0.64; p>0.05). Conclusion: Self-questionnaire to identify lifestyle pattern and also random blood glucose screening is well method for preventive way as an early warning of T2DM. This screening must be conduct regularly, so that everyone known its risk factor.